Genealogy, Archive, Image. Interpreting Dynastic History in Western India, c.1090-2016 - Jhala, Angma (De Gruyter, 2017)
'Genealogy, Archive, Image' addresses the ways in which history and tradition are 'reinvented' through text, memory and painting. It examines the making of dynastic history in the kingdom of Jhalavad, situated in Gujarat, western India, over the longue durée, from the eleventh to twentieth centuries. The essays critique a collection of contemporary miniature paintings, which chart the dynastic history of Jhalavad's rulers and the textual and ethnographic archive upon which they are based. A multidisciplinary work, it crosses the boundaries of history, anthropology, folklore and mythology, gender, musicology, literary studies, and visual, film and digital media. The essays draw upon a variety of voices, spanning various religious and ethnic communities, including Hindus, Muslims, Jains, Parsees and Siddhi Africans, and caste identities, such as that of the bard, ballad singer, king, priest, court chronicler, soldier, mason and drummer.